Implementasi WebRTC Pada Sistem Broadcast Pembelajaran Untuk Menampilkan Bahasa Isyarat - Farouq Alamsyah; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In public schools, deaf people have communication problems when teaching in class. Teaching in class depends on using verbal communication between students and students. This means that students and other students have communication problems with deaf people. Based on these problems, we need tools that can help students, especially the deaf in the classroom. The system in question has the main feature of converting sound into sign language in real-time while learning takes place. The system was built using Web Real-time Communication (WebRTC) is a protocol for sending data in real-time. WebRTC's Application Programming Interface (API) is free and is supported by all web browsers. In this research, network system performance testing is performed to determine the quality of the system and the use of computer resources on the side of the user. Testing is divided into two test environments namely local networks and different networks. In each testing environment, four stages of testing are conducted based on the number of users, namely 5 students, 10 students, 20 students, and 40 students. The test results show that there is an increase in jitter, delay, packet loss, memory, and processor for each additional student.